Application of multidisciplinary team management by using the PDCA approach in blood glucose control of elderly patients with type 2 diabetes (多学科PDCA血糖管理模式在老年2型糖尿病患者中的应用) - FAN Meihong (樊美红); LI Yuxia (李玉霞) (中西医结合护理)
Objective To investigate the effect of multidisciplinary team management by using the PDCA approach in blood glucose control of elderly patients with type 2 diabetes in the non-endocrinology department. Methods Totally 120 elderly patients with type 2 diabetes in the non-endocrinology department were randomly divided into the observation group and control group, with 60 cases in each group. All patients received routine nursing, insulin-pump therapy and Flash Glucose Monitoring, and those in the observation group were given multidisciplinary team management by using the PDCA approach. The incidence of hypoglycemia and patient satisfaction with nursing were compared between two groups. Results The incidence of hypoglycemia in the observation group was lower than that in the control group (P＜0. 05). The satisfaction rate in the observation group was higher than that in the control group (P＜0. 05). Conclusion The multidisciplinary team management by using the PDCA approach is potentially effective to reduce the incidence of hypoglycemia among elderly patients with type 2 diabetes mellitus, and improve patient satisfaction with nursing service. (目的 探讨多学科PDCA综合血糖管理模式在非内分泌科老年糖尿病患者中应用效果。方法 收集2021年6月—12月非直属内分泌医学科室住院糖尿病患者120例, 随机分为观察组和对照组, 各60例。在常规护理的基础上, 对照组给予外用胰岛素泵及“瞬感”血糖监测, 观察组在对照组的基础上采用多学科PDCA综合血糖管理模式。观察两组患者低血糖发生率, 评价患者对护理工作满意度。结果 观察组低血糖发生率低于对照组(P＜0. 05)。观察组满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 采用糖尿病多学科PDCA综合血糖管理模式能进一步降低非直属内分泌科室糖尿病住院患者低血糖发生率, 提升住院患者对护理工作的满意度, 促进护理服务质量改善。)